Analysis of directions of revitalization of winery Enterprises (Collection of scientific works «Scientific Problems of Architecture and Urban Planning» | ODABA, 2026)
In the context of modern urbanization processes, the priority of sustainable urbandevelopment and the actualization of issues of cultural heritage preservation, the revitalization ofindustrial facilities, in particular historical wineries, is of particular importance. Such complexesform a unique segment of industrial architectural heritage, combining production, cultural andlandscape characteristics and closely related to local identity, historical traditions and spatialstructure of territories. In the context of the transformation of economic models, deindustrializationand the development of creative industries, former wineries are increasingly being considered aspotential centers of socio-cultural activity, tourism, public initiatives and spatial renewal of theurban environment.The aim of the article is to analyze modern approaches and practices of revitalization ofhistorical wineries with a focus on architectural and urban planning directions of adaptive reuse andprinciples of sustainable development.The study considers key problems of preserving the historical and architectural value ofobjects, the features of their functional transformation, the formation of new scenarios of use andthe integration of modern needs of the community, the market and tourism infrastructure. Specialattention is paid to the issues of functional mix, interaction with adjacent urban spaces and the roleof revitalized complexes in the formation of a multifunctional urban environment. The evolution ofapproaches to the revitalization of wineries in European and international practice is summarized,and their potential as a tool for sustainable spatial development and improving the quality of theurban environment is determined. The results obtained can be used in the practice of architecturaland urban design, redevelopment of industrial areas and strategic planning of the development ofhistorical production complexes.
Keywords: revitalization; adaptive reuse; directions\methods; industrial heritage; wineries; architectural and urban strategies; sustainable development; cultural identity; development of territories